Activity of arachidonic acid and gamma-linolenic acid on human gliomas - Williams, Jillian R. (The University of Edinburgh, 2002)
Despite recent advances in tumour cell biology, the prognosis for patients suffering from malignant glioma remains poor. Although primary glioma rarely metastasises outside the central nervous system (primary being defined as the mass of tumour cells at the original site of the neoplastic event) median survival of adults is less than 1 year after diagnosis.The efficacy of existing therapeutic interventions is limited by poor penetration of chemotherapeutic drugs across the blood brain barrier, the inherent radioresistance of glioma tissue and the infiltrating nature of the tumour. Further progress is likely to be achieved through analysis of the complex biology of these tumours and the development of novel therapeutic strategies. The purpose of this study was to investigate the therapeutic potential of the n-6 essential fatty acids arachidonic acid and gamma-linolenic acid, which may inhibit tumour proliferation by acting as substrates for the production of potentially cytotoxic reactive oxygen intermediates and stimulating apoptotic cell death, both alone and in conjunction with radiation. Experiments were undertaken to investigate the effects of exogenous arachidonic acid and gamma-linolenic acid on cellular peroxidation, proliferation, viability and apoptosis. These investigations were carried out on single cell suspensions of morphologically heterogeneous fresh human glioma tissue and associated normal brain, human phagocytes and the rat C6 glioma cell line. It was shown that oxidative activity was impaired in human glioma tissue. Addition of 4-40μM arachidonic acid and gamma-linolenic acid induced a concentration dependant increase in tumour reactive oxygen intermediate production and apoptotic activity. Although the kinetics of reactive oxygen intermediate formation in the presence of arachidonic acid and gamma-linolenic acid followed an exponential function in both normal and tumour cell preparations, tumour cells showed a significantly higher sensitivity to exogenous essential fatty acid stimulus. The kinetics of this stimulation were grade dependent, with high grade tumours responding in a more rapid and sustained manner in comparison with lower grade tumours. The morphological heterogeneity of the human glioma preparations was confirmed with immunohistochemical analysis and flow cytometry using monoclonal and polyclonal anti-Glial Acidic Fibrillary Protein (GFAP). GFAP positive cells responded to exogenous arachidonic acid and gamma-linolenic acid with increased reactive oxygen intermediate production, indicating a high sensitivity of glioma cells to essential fatty acid stimulus. Reactive oxygen intermediate production was also investigated in phagocyte preparations of patients undergoing pulmonary resection for lung cancer. It was found that reactive oxygen intermediate generation was stimulated in patient and control phagocytes by exogenous 1 -40μM arachidonic acid and gamma-linolenic acid both pre and post-operatively. Increased reactive oxygen intermediate formation was detected in the cell population identified as leukocytes in preparations of human primary glioma, although this response was less than that of associated tumour. It was also found that surgery was associated with an increase in phagocyte reactive oxygen intermediate at 2 and 7 days post-operatively in lung cancer patients. The interactive effects of arachidonic acid, gamma-linolenic acid and therapeutic radiation were demonstrated in the rat C6 glioma cell line. The rate ofreactive XVI oxygen intermediate production in response to exogenous arachidonic acid and gamma-linolenic acid increased within the first hour, and elevated oxidative activity was detected for up to three hours. However, a different pattern ofreactive oxygen intermediate generation was observed in response to radiation alone. Similarly, an early apoptotic response was observed following exogenous arachidonic acid and gamma-linolenic acid stimulation. In comparison, radiation induced stimulation of apoptosis occurred over the 12 hour period of incubation and was maximal between 6 and 8 hours post-irradiation. An enhanced radiation response was observed when the stimulation of apoptosis induced by essential fatty acid stimulus alone was low, suggesting that essential fatty acids and radiation may interact to potentiate reactive oxygen intermediate generation and apoptosis. In conclusion, this study has provided evidence that glioma tissue has low basal oxidative activity in comparison with associated normal brain, and that addition of exogenous arachidonic acid and gamma-linolenic acid stimulates peroxidative and apoptotic activity in glioma tissue a grade dependant manner. Studies on the cellular heterogeneity of human glioma samples indicate that the stimulation ofreactive oxygen intermediate production by exogenous arachidonic acid and gamma-linolenic acid occurs in GFAP positive cells. This indicates high sensitivity of human glioma to exogenous essential fatty acid stimulus. Phagocyte populations from lung cancer and malignant glioma patients also respond with increased reactive oxygen intermediate production to exogenous arachidonic acid and gamma-linolenic acid, although the magnitude of this increase is less than that observed for tumour cells. In addition, there is evidence ofpotentiation ofthe oxidative and apoptotic response of the rat C6 cell line to exogenous arachidonic acid and gamma-linolenic acid in the presence of therapeutically relevant doses ofradiation. These results are consistent with a clinical role for arachidonic acid and gamma-linolenic acid in the treatment of malignant glioma.
The activity of arachidonic acid and gamma-linolenic acid on human gliomas